2021
DOI: 10.24191/jeeir.v9i2.12413
|View full text |Cite
|
Sign up to set email alerts
|

Islamic estate planning in the industrial revolution 4.0 era: Issues and challenges

Abstract: The development of the Industrial Revolution 4.0 has contributed to creating various technologies for economic progress. This includes the field of Islamic estate planning, such as will and trust. However, the technology developed to meet the Muslim community's property planning needs is still in its infancy until now. Therefore, the purpose of this study is to investigate the issues and challenges faced by trust institutions in Malaysia in facing Islamic estate planning in the Industrial Revolution 4.0 era. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Therefore, they do not plan systematically either through a will, Hibah , waqf or trust instrument. A study conducted by Abdullah et al (2021) also showed that the knowledge and implementation of the trust instruments among the community is still at a low level.…”
Section: Estate Administration Issuesmentioning
confidence: 99%
“…Therefore, they do not plan systematically either through a will, Hibah , waqf or trust instrument. A study conducted by Abdullah et al (2021) also showed that the knowledge and implementation of the trust instruments among the community is still at a low level.…”
Section: Estate Administration Issuesmentioning
confidence: 99%
“…The study chose to focus on Muslims in Klang Valley since the prevalence of dispute and pending distribution of Muslims estate is reported to be at approximately 86% (Ahmad et al, 2019). This percentage is considered as high among its population second only to Kedah (Abdullah et al, 2021). It is hoped that the findings from this study can provide some understanding of the factors influencing intention to give hibah among the Muslim community and such findings can be leveraged by the authorities and interested agencies in promoting hibah giving and enhancing wealth management practices in Malaysia (Abdullah et al, 2021).…”
Section: Problem Statementmentioning
confidence: 99%
“…This percentage is considered as high among its population second only to Kedah (Abdullah et al, 2021). It is hoped that the findings from this study can provide some understanding of the factors influencing intention to give hibah among the Muslim community and such findings can be leveraged by the authorities and interested agencies in promoting hibah giving and enhancing wealth management practices in Malaysia (Abdullah et al, 2021). Indirectly, with better wealth management, property disputes cases and incidents of widows and children being left in dire financial situation pending the distribution of estate can be lessened and their welfare are better taken care of.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Every year scholars will raise the issue of unclaimed property and now it has been found that almost RM90 billion worth of real estate has not been claimed by the rightful and legitimate heirs (Roslan & Ahmad, 2022). In addition to other issues such as high administrative costs (Ab Rahman et al, 2019) and difficulties during the administration process of the inheritance (Wan Hassin et al, 2016) were also be the main issue that is often heated from the point of view in understanding of the heirs who lack in knowing the division of their inheritance (Abdullah et al, 2021) and the lack of responsibility among the heirs in committing to manage and resolve matters of their inheritance (Wajis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%